A PLGA-reinforced PEG in situ gel formulation for improved sustainability of hypoglycaemic activity of glimepiride in streptozotocin-induced diabetic rats. Issue 1 (December 2017) - Ahmed, Osama; El-Say, Khalid; Alahdal, Abdulrahman
Abstract Glimepiride (GMD) is a third-generation sulfonylurea derivative and one of the top three most-prescribed oral antidiabetic drugs. The need for a depot formulation exists, and a safe and effective antidiabetic therapy is the goal of this study. The aims were to design a depotin situ gel (ISG) formulation and investigate the main factors that control the initial burst and sustain the GMD effect using the Box-Behnken design. The studied factors were polymer percent (X1 ), plasticizer percent (X2 ) and benzyl benzoate percent in N-methyl-2-pyrrolidone (X3 ). The results revealed that X2 is the only factor that showed significant effects on all investigated responses. Scanning electron microscopy images showed that an increase in PEG % improved the smoothness and reduced the porosity of the ISG formulation surface. The GMD plasma levels in diabetic rats revealed no significant difference (p < 0.05) between the maximum GMD plasma concentrations of the optimized GMD-ISG formula (10 mg/ kg) and oral marketed GMD tablets (1 mg/kg). This result ensures that the optimized formula does not exceed the maximum safe plasma concentration. In addition, the optimized GMD-ISG formulation showed a depot effect that lasted for 14 days post-injection. This approach to controlling GMD release using anin situ forming system could be useful for improving patient compliance and diabetes treatment effectiveness.